The Police Composite Sketch - Mancusi, Stephen (Humana Press : Imprint: Humana, 2010)
The police composite sketch, one of the most crucial investigative tools in law enforcement, is developed during a composite session-an intense display of communication and art in which the words of a witness are transformed into the features of a suspect. Despite the incredible technological leaps made in investigative work, the forensic science of composite sketching still relies on the basic elements of drawing skill, interpretive ability and the spoken word. The Police Composite Sketch is a comprehensive manual on how to conduct a complete composite session. Through an array of case studies, it details several disciplines that comprise this specialized forensic art, including composite sketching, image modification, age progression, facial comparison analysis, demonstrative evidence and postmortem/skull reconstruction. It also explores how to intuit insights that are often inadvertently revealed by witnesses, victims and perpetrators during the composite session. In addition, this book discusses other relevant topics, such as the three-stage drawing technique, witness and victim types, descriptive terminologies, managing composite sessions. Complete with numerous illustrations and drawing tips, this seminal work offers a general composite session philosophy and specific session strategies to both experienced and aspiring forensic artists as well as any lay reader intrigued by this fascinating skill.